Does the birth of a first child reduce the father's offending?. Issue 1 (March 2015) - Theobald, Delphine; Farrington, David P; Piquero, Alex R
A little investigated correlate of persistence and desistance is the effect of parenthood. Research suggests that for females particularly, parenthood plays an important role but the evidence for males is mixed. Yet, prior studies have not considered potential selection effects. This paper seeks to overcome this limitation by examining the effects of having a child on offending using propensity score matching, with data from the Cambridge Study in Delinquent Development, a longitudinal study of 411 South London males followed since childhood. Findings indicate that, while there are reductions in offending from several years before the child's birth to several years after the child's birth, the effects are not large. Further analyses examining 'shotgun' marriages show that reductions in offending are larger than for non-'shotgun' marriages. Also, if a man remains with the child for at least five years, then reductions in convictions are greater than when he does not.